Pneumothorax, Pneumomediastinum, and Cervical and Facial Massive Emphysema Secondary to Colonoscopy: A Rare Complication of Colonoscopy - Ruben Daniel Perez Lopez; Julian Vargas Flores; Lenin de Jesus Orbe Garibay; Hugo Fernando Narvaez Gonzalez (Case Reports in Gastrointestinal Medicine)
Background. Colonoscopy is a resource used for the diagnosis, treatment, and monitoring of benign and malignant colorectal pathologies. The incidence of perforation is 0.03%–0.65% in diagnostic colonoscopy; however, the incidence can be up to 10 times higher in therapeutic interventions, such as polypectomies, increasing the risk of complications up to 0.07–2.1%. Materials and methods. Case report of a 71-year-old female who presents a rare complication due to a perforation in the sigmoid which developed pneumoperitoneum, pneumomediastinum, pneumothorax, and massive subcutaneous emphysema as a complication of a diagnostic colonoscopy where a biopsy of a friable lesion was performed. Results. A 71-year-old female that went to the emergency room due to acute generalized abdominal colic spasm pain with a duration of 7 hours, associated with significant abdominal distension, malaise, diaphoresis, progressive dyspnea, and massive subcutaneous emphysema that developed after performing panendoscopy and colonoscopy for diverticulosis follow-up. An abdominal CT scan with double contrast was performed, reporting suggestive data of hollow viscus perforation, pneumoperitoneum, pneumomediastinum, pneumothorax, and massive subcutaneous emphysema in the thorax, neck, and skull base. She underwent an exploratory laparotomy finding a perforation in the sigmoid for which sigmoidectomy was performed, and for the pneumothorax and pneumomediastinum, endopleural tubes were placed in both hemithoraxes. The massive subcutaneous emphysema subsided with observation and oxygen. Conclusion. A rare complication of the use of colonoscopy as a diagnostic and therapeutic method is presented. The purpose of presenting this case is for the doctor who performs these interventions to suspect this complication in a timely manner, not delaying the diagnosis and carrying out an urgent therapeutic approach as in this case with exploratory laparotomy, finding the perforation site and carrying out the corresponding surgical management. We demonstrated that massive subcutaneous emphysema can be managed with observation if there is no other alarm data evident that required another surgical approach.